Effect of Product, Price, Location and Tourism Promotion of Interest in Visiting Lake Toba Tourist Attraction - Marisa Sianipar (Institute of Computer Science (IOCS), 2019)
North Sumatra has the potential of natural beauty as well as historical tourism, customs and regional uniqueness. Efforts made in the development of tourism in North Sumatra is to reform several important aspects. Tourism development has the concept of 3A, namely: Attractions, Access and Amity. To increase tourist visits and return visits to Lake Toba it is necessary to study whether tourism products carried by the North Sumatra Government can create a positive image in the minds of tourists. The research objectives are 1) to determine the effect of the product on the interest of visiting the Lake Toba tourist attractions, 2) to know the influence of the price on the interest of visiting the Lake Toba attractions, 3) to know the influence of the location on the interest of visiting the Lake Toba Tourism, 4 ) determine the effect of tourism promotion on the interest of visiting the Lake Toba tourist attractions and 5) know the influence of the product, price, location and tourism promotion on the interest of visiting Lake Toba tourism. This study uses quantitative descriptive methods aimed at obtaining a picture of the influence of the product, price, location and tourism promotion as well as its impact on the interests of tourist visits. The study population was archipelago tourists who were visiting tourist in Lake Toba in the period of May to June 2019 as many as 35,000 people, using a purposive sampling technique calculated with the Slovin formula the sample size was 100 people. The results of the study are multiple linear regression equations are: Y = 3.080 + 0.470X1 + 0.007X2 + 0.045X3 + 0.254X4, partial t-test obtained value of tcount value of 5.678 and ttable value of 1.660 where value 5.678> 1.660 and sig value 0.000 <.000 0.05, the product t-test value was 4.064 and the t-table value was 1.660 where the value was 4.064> 1.660 and the sig value was 0.005 <0.05, the location t-test value was 2.354 and the table value was 1.660 where the value was 2.354> 1.660 and the sig value was 0.007 <0, 05, the value of promotion count is 2.172 and the table value is 1.660 where the value is 2.172> 1.660 and the sig value is 0.032 <0.05, the Fcount value is 44.735 and the F table value is 2.464 where the value is 44.735> 2.464 and the sig value is 0.000 <0.05. Furthermore, the Adjusted R Square value is 0.853 or 85.30%, meaning that the research variable contributes or contributes in explaining the Interest in Returning to Lake Toba Tourist Attraction by 85.30% while the remaining 14.70% is influenced by other factors outside research. The conclusion of the research is that the product has a significant effect and is the dominant variable that influences the interest in returning to Lake Toba, the price has a significant effect on the interest in visiting back to Lake Toba, the location has a significant effect on the interest in visiting back to Lake Toba, Toba and simultaneous product, price, location and promotion have a significant effect on the interest of visiting Lake Toba again.